The benefit of green building for cost efficiency - David Kiki Baringin M T Samosir; Etty Murwaningsari; Yvonne Augustine; Sekar Mayangsari (Goodwood Publishing, 2020)
Purpose: The Study seeks to implement the green building concept especially in office buildings and malls. Further, this research also investigates the measurement of the green building efficiency that conforms with accounting theories. Research methodology: This study used a mixed method for collecting data by sending questionnaire to the number of respondents of this study. The data from the questionnaires were collected by using simple arithmetic techniques and graphics techniques. Results: This study found that most buildings having already implemented the concept of green buildings gained efficiency benefits from both environmental and operational cost. The respondents’ knowledge and experience influence the success in implementing 6 criteria of green building including Appropriate Site Development (ASD), Energy Efficiency and Conservation (EEC), Water Conservation (WAC), Material Resources and Cycle (MRC), and Indoor Health and Comfort (IHC). Limitations: This study indicates weaknesses for further improvements especially in terms of the quantity of respondents, the respondents’ willingness to complete the questionnaire Contribution: Green building is one of the solutions to minimize the impact of global warming or unhealthy workplace environment. Keywords: Green buildings, Sustainability, Energy efficiency, Energy conservation